2009
DOI: 10.1111/j.1365-2265.2009.03753.x
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac calsequestrin gene (CASQ2) is up‐regulated in the thyroid in patients with Graves’ ophthalmopathy – support for a role of autoimmunity against calsequestrin as the triggering event

Abstract: The skeletal and cardiac calsequestrin proteins share 68.4% amino acid homology. Previous work has shown that RNA levels of skeletal muscle calsequestrin are 4.7 times higher in extraocular muscle (EOM) than in masticatory skeletal muscle (jaw), and cardiac calsequestrin is expressed 2.7 times more in EOM. We postulate that up-regulation of casq2 gene in the thyroid of patients with GH may lead to the production of autoantibodies and sensitized T-lymphocytes, which cross-react with calsequestrin in the EOM of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…This suggests functional differences in terms of Ca 2+ storage and turnover in EOM. Moreover, Casq2 has been suggested as target in autoimmune thyroid disease with eye involvement (Wescombe, et al, 2009). In fast EOM fibers Casq2 may also be present and may be co-expressed with the fast fiber isoform Casq1 in at least some EOM fiber-types.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests functional differences in terms of Ca 2+ storage and turnover in EOM. Moreover, Casq2 has been suggested as target in autoimmune thyroid disease with eye involvement (Wescombe, et al, 2009). In fast EOM fibers Casq2 may also be present and may be co-expressed with the fast fiber isoform Casq1 in at least some EOM fiber-types.…”
Section: Discussionmentioning
confidence: 99%
“…Porter et al [26] showed that CASQ1 is expressed 4.6 times more in extraocular muscles than skeletal muscles elsewhere. In recent micro-array studies in which we compared expression of genes in patients with Graves' hyperthyroidism with and without ophthalmopathy, we found that the gene for CASQ2 was significantly upregulated (2.8-fold) in patients with ophthalmopathy compared to those without eye disease [27]. While the gene for CASQ1 was also upregulated in patients with ophthalmopathy (4.1-fold) this was not statistically significant [27].…”
Section: Introductionmentioning
confidence: 85%
“…Bostwick et al [36] found elevated levels of IGFBP5 when investigating the fibroblasts in fibrotic lung tissue, and that the expression of IGFBP5 was increased in liver fibrosis. However, IGFBP5 was downregulated in GO thyroid tissue [37]. IGFBP5 has different functions, which are dependent on the cell and tissue type [38,39].…”
Section: Characterization Of Eom-mpcs From Go Patientsmentioning
confidence: 92%